DIDACTICS STUDY OF THE DEPARTMENT OF SYSTEMATICS OF BLUE-GREEN ALGAE (CYANOPHYTA) - Abdumovlon Abduvalievich Temirov; Fazilatkhon Sheralibek kizi Sharipova; Durdona Salim kizi Bustonova; Navbakhor Davron kizi Bakhodirova (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the issues of methodological features of studying the section of algae taxonomy, the formation of theoretical knowledge and practical skills in conducting research in the field of taxonomy, ecology of algae, studying the cycles of their development, developing skills in conducting field and laboratory algological studies, using high-tech laboratory equipment in the course of solving scientific problems in the field of algology, the formation of professional training for independent scientific, research and pedagogical activities, the essence of modern methods for collecting quantitative and qualitative samples of planktonic, periphytic and benthic algae, laboratory processing of material, taxonomic and morphometric processing of samples.